Pharmacokinetics during therapeutic hypothermia for neonatal hypoxic ischaemic encephalopathy: a literature review - Karel Allegaert; Isabelle Claire Lutz; Jan N de Hoon; Heleen Marynissen (BMJ Publishing Group, 2020)
Background Neonatal hypoxic ischaemic encephalopathy due to perinatal asphyxia, can result in severe neurodevelopmental disability or mortality. Hypothermia is at present the only proven neuroprotective intervention. During hypothermia, the neonate may need a variety of drugs with their specific pharmacokinetic profile. The aim of this paper is to determine the effect that hypothermia for neonates suffering from hypoxic ischaemic encephalopathy has on the pharmacokinetics and to what extent dosing regimens need adjustments.Method A systematic search was performed on PubMed, Embase and Cochrane Library of literature (2000-2020) using a combination of the following search terms: therapeutic hypothermia, neonate, hypoxic ischemic encephalopathy and pharmacokinetics. Titles and abstracts were screened, and inclusion/exclusion criteria were applied. Finally, relevant full texts were read, and secondary inclusion was applied on the identified articles.Results A total of 380 articles were retrieved, and 34 articles included after application of inclusion/exclusion criteria and duplicate removal, two additional papers were included as suggested by the reviewers. Twelve out of 36 studies on 15 compounds demonstrated a significant decrease in clearance, be it that the extent differs between routes of elimination and compounds, most pronounced for renal elimination (phenobarbital no difference, midazolam metabolite −21%, lidocaine −24%; morphine −21% to −47%, gentamicin −25% to −35%, amikacin −40%) during hypothermia. The data as retrieved in literature were subsequent compared with the dosing regimen as stated in the Dutch paediatric formulary.Conclusion Depending on the drug-specific disposition characteristics, therapeutic hypothermia in neonates with hypoxic ischaemic encephalopathy affects pharmacokinetics.